Dear nobody - Doherty, Berlie (New York : Beech Tree Books, 1994)
Eighteen-year-old Chris struggles to deal with two shocks that have changed his life, his meeting the mother who left him and his father when he was ten and his discovery that he has gotten his girlfriend pregnant.
Booklist.
Horn Book Starred.
Wilson's Junior High School.
Young Adult
Keywords: Mothers and sons -- Fiction; Pregnancy -- Fiction; Unmarried mothers -- Fiction; Mother-son relationship -- Fiction; Pregnancy -- Fiction; Unmarried mothers -- Fiction